Acromegaly with negative immunostaining for growth hormone on the contrary to silent somatotroph tumor - Ozisik, Hatice; Yurekli, Banu Sarer; Kutbay, Nilufer Ozdemir; Altun, Ilker; Ertan, Yesim; Saygılı, Fusun (International Surgery Journal, 2017)
Silent somatotropinomas are not rare. On the contrary to that, the absence of GH immunostaining in acromegaly has not been well defined. So, we would like to to draw the clinician’s attention to such an entity through a case of acromegaly with negative GH staining.